Bafilomycin M, a new cytotoxic bafilomycin produced by a Streptomyces sp. isolated from a marine sponge Theonella sp. Issue 43 (26th October 2016) - Chen, Yu-Hsin; Lu, Mei-Chin; Chung, Hsu-Ming; Weng, Ching-Feng; Su, Jui-Hsin; Yang, Yu-Tang; Su, Yin-Di; Chang, Yu-Chia; Kuo, Jimmy; Wu, Yang-Chang; Sung, Ping-Jyun
Graphical abstract: Highlights: A new bafilomycin, bafilomycin M, is produced from a Streptomyces sp. GIC10-1. Structure of bafilomycin M was established by interpretation of spectroscopic data. Bafilomycin M showed cytotoxicity against K562, HL-60, SUPT-1, and LNCaP cells. Abstract: A new 16-membered diene macrolide, bafilomycin M (1 ), was produced from a Streptomyces sp. GIC10-1, which was originally isolated from a marine sponge Theonella sp. The structure of1 was established by spectroscopic methods and this compound was found to exhibit cytotoxicity toward K-562, HL-60, SUPT-1, and LNCaP tumor cells with IC50 values 0.060, 0.011, 0.047, and 0.389 μg/mL, respectively.